Study on epilithic diatoms in the Balikli Tohma Creek (Darende/Malatya in Turkey) - Caglar, M.; Pala, G.; Selamoglu, Z. (Iranian Fisheries Science Research Inst-Ifsri, 2017)
[Abstract Not Available]
Keywords: Balikli Tohma Creek; Diatom; Epilithic; Algae